Early fatal hemoptysis after first-dose, first-line pembrolizumab in a central lung cancer: did tumor shrinkage matter?. (16th January 2019) - Facchinetti, Francesco; Majori, Maria; Sabato, Mariangela; Gnetti, Letizia; Tiseo, Marcello
A patient diagnosed with centrally located advanced lung adenocarcinoma with signs of large vessels infiltration, strongly expressing PD-L1, was candidate to first-line pembrolizumab. He had not complained of any bleeding manifestation before immunotherapy. 5 days after the first dose of pembrolizumab, the patient experienced massive, fatal hemoptysis. Given the central localization of the tumor and the strong PD-L1 expression, a contribution of rapid disease shrinkage is envisaged in determining the fatal hemorrhagic event. An attentive clinical attitude should be dedicated in centrally located and vessel-infiltrating tumors strongly expressing PD-L1 and candidate to anti-PD-1/PD-L1 agents.